Laser direct writing of modulation-doped nanowire p/n junctions. (4th November 2016) - Nam, Woongsik; Mitchell, James I; Xu, Xianfan
Abstract: We demonstrate a single-step, laser-based technique to fabricate axial modulation-doped silicon nanowires. Our method is based on laser-direct-write chemical vapor deposition and has the capability to fabricate nanowires as small as 60 nm, which is far below the diffraction limit of the laser wavelength of 395 nm, with precise control of nanowire position, length, and orientation. By switching dopant gases during nanowire writing, p–n junction nanowires are produced. The p–n junction nanowires are fabricated into multifinger devices with parallel metal contacts and electrically tested to demonstrate diode characteristics.